Dual-Band Rectifier Design With High Efficiency Using Simple Dual Band-Stop Network for Wireless Power Transfer - Dang-An Nguyen; Yujin Choi; Chulhun Seo (IEEE Access)
This paper presents a novel structure for designing a dual-band (DB) rectifier with high efficiency and compact size for wireless power transfer. The proposed circuit employs a simple dual band-stop network cascaded by only two transmission lines (TLINs) which can yield open-circuit termination simultaneously for the second harmonics of both two separate frequency bands, enabling an efficient DB power recycling mechanism with minimum insertion loss for power conversion efficiency (PCE) enhancement. The closed-form formulas are derived to extract the TLIN parameters with a low complexity. A rectifier based on a Schottky diode model BAT15-03W is simulated and measured for verification at two target operating frequencies of 0.915 GHz and 2.45 GHz. The measured results show peak PCE of 79.2% and 77.8% observed at 0.9 GHz and 2.36 GHz, respectively. Moreover, wide dynamic range for PCE>50% is equally recorded at both two frequencies with 17.5 dB. Also, the proposed rectifier exhibits a small electrical size of $0.102λ × 0.105λ $ , indicating advantages in terms of high PCE and compactness, as compared to the other similar designs.